Periodic oral examinations and panoramic radiographs in edentulous elderly men - Lloyd, Patrick M.; Gambert, Steven R. (Oral surgery, oral medicine, oral pathology, 1984)
Oral and panoramic radiographic examinations were performed on eighty-six edentulous elderly men residing in a government-sponsored skilled nursing facility. Clinical examinations revealed eleven findings in eleven subjects, 12.8% of the total number examined. panoramic radiographs were taken compared with those available from previous years. Of the 173 radiographs available for review, twenty-two films of seven subjects yielded significant findings. In no case did there appear to be progression of the radiographic findings over time, and no findings required intervention. Data suggest that the availability of ongoing dental care through consultations may reduce the prevalence of findings on periodic oral examination.